ETHICAL LEADERSHIP DAN KOMITMEN ORGANISASI SEBAGAI PREDIKTOR INTENSI TURNOVER KARYAWAN - Alvia Diah Fitriana; Ruseno Arjanggi (Proyeksi: Jurnal Psikologi, 2020)
The purpose of this study was to determine the relationship between Ethical Leadership and organizational commitment to employee turnover intention. Turnover intention is a desire to stop or get out of his work and wish to change jobs. The subjects used in the study were 150 employees. The method used for sampling uses a purposive sampling technique. The scale used at the time of this research was the turnover intention scale with reliability 0.796, Ethical Leadership scale with reliability 0.879, and organizational commitment scale with reliability 0.802. Data analysis used in this study is regression analysis with two predictors and partial correlation. The first hypothesis test results obtained a score of F = 26.217, R = 0.613, and p = 0.000 (p <0.05). Thus it can be seen that there is a relationship between Ethical Leadership and organizational commitment to employee turnover intensity. The second hypothesis obtained rx1y = 0.274 and a significance of 0.009 (p <0.05). These results prove that there is a positive relationship between Ethical Leadership and turnover intensity. The third hypothesis obtained the results of rx2y = -0.612 with a significance of 0,000 (p <0.05). The results explained prove that there is a negative relationship between organizational commitment and turnover intention.